Strategi Peningkatan Kapasitas Peternak Domba melalui Kampus Desa Tematik di Desa Neglasari, Bogor, Jawa Barat - Pudji Muljono; Hana Indriana; Novindra; Yannefri Bachtiar; Mintarti (Jurnal Penyuluhan, 2022)
The process of disseminating innovation so that it can be quickly responded by the user community needs to be designed in such a way that it can produce relatively permanent changes in behavior. This study aims to analyze how the strategy of increasing the capacity of sheep farmers through the thematic village campus program in Neglasari Village, Bogor. The research was designed as action research at the study site, accompanied by the use of survey methods with a quantitative approach and supported by qualitative data. The selection of study sites was carried out purposively. The process of collecting data was carried out on sheep breeders, members of women's farmer groups, informants and related stakeholders. The Village Campus Program has accelerated the technology education process produced by the campus to the community, becoming a vehicle for lecturer service, linkage with faculty programs or study programs. In order for this program to be sustainable, it is necessary to involve various parties such as alumni, local leadership, based on user needs, as well as conducting regular meetings on a programmed basis.